Magnezyum alaşımlarının tıg kaynak özellikleri - Eratıcı, Erhan (My University, 2011)
MAGNEZYUM ALAŞIMLARININ TIG KAYNAK ÖZELLİKLERİ Magnezyum en düşük özgül ağırlığa sahip metal olduğu için magnezyum alaşımları mükemmel özgül dayanıma sahiptir. Bu alaşımların dökümü, talaş kaldırılması, sıcak şekillendirilmesi, titreşim söndürme kabiliyeti ve geri kazanım özellikleri çok iyidir. Bu metalin maliyeti yüksek, oda sıcaklığı sünekliği, korozyon direnci ve aşınma direnci çok düşüktür. Bu ve sürünme direnci handikaplarından dolayı tüketimi ve üretimi çok azdır. Magnezyum alaşımlarının son yıllardaki ekonomik krizler ve ticaretin globalleşmesi otomotiv sektöründe magnezyumun kullanımını arttırmıştır. Bu artışın önümüzdeki yıllarda da artarak devam etmesi beklenmektedir. Magnezyum alaşımlarına halen bakım onarım kaynak uygulamaları yapılmaktadır. Bu alaşımların tüketiminin gelişmesi için ucuz ve kaliteli seri üretim kaynak yöntemlerine ihtiyaç vardır. Halen magnezyum alaşımlarına TIG ve lazer kaynağı yaygın olarak uygulanmaktadır. Yeni kaynak yöntemleri uygulamaları için çalışmalar yapılmaktadır. Magnezyum alaşımlarının TIG kaynağında porozite ve sıcak çatlak en çok karşılaşılan kaynak hatalarıdır. Ayrıca magnezyum alaşımlarının TIG kaynağında sınırlı nüfuziyet derinliği önemli bir handikap oluşturmaktadır. TIG kaynak yönteminde kaynak parametrelerini uygun seçmek suretiyle kaynak hataları önlenebilmektedir. Kaynak nüfuziyetini arttırmak için flaks kullanımı büyük kazançlar elde etmeye yaramıştır. Magnezyum alaşımlarının TIG kaynağı sırasında kaynak parametrelerinin (akım şiddeti, kaynak ilerleme hızı, gerilim ve polarite) dikiş boyutu ve kaynak hata oluşumu üzerindeki etkileri incelenmiştir. TIG kaynağı sırasında kullanılan flaksın kimyasal bileşimi, konsantrasyonu ve tane boyutunun dikiş nüfuziyet üzerindeki etkileri deneysel olarak incelenmiştir.

PROPERTIES OF MAGNESIUM ALLOYS TIG WELDING Magnesium is the lightest of all the engineering materials, having a density of 1.74 g/ cm3. It is lighter than aluminium and over four times lighter than iron. This low density makes magnesium and its alloys attractive for the industry. This low density causes excellent static specific strength and very good specific stiffness. The high specific strength of magnesium alloys is a safety advantage against steels and other light weight materials. The specific stiffness of the magnesium alloys is a little bit less than steel but higher than light weight materials. Commercial die cast magnesium alloys have better damping properties than steels and aluminium alloys. Coupled with low weight and inertia, this reduces vibration and resonance in moving components. Most magnesium alloys have very good castability and uniformity of properties in various section thicknesses and can be cast by all current casting processes. Most of the common magnesium alloy components are produced by high pressure die casting processes. Magnesium alloys can be machined faster than any other engineering metal. Magnesium components and scraps can be recycled to the same high purity and quality standards as primary alloys. Magnesium alloys are easily rolled, extruded or forged at elevated temperatures. Several drawbacks have limited the growth of magnesium usage in the industry. The key factor that inhibits the massive use of magnesium is its relatively high price. Magnesium has a hexagonal closed packed (HCP) lattice, therefore pure magnesium and its cast alloys have limited ductility at the room temperature. Magnesium and its alloys are extremely susceptible to galvanic corrosion, which can cause severe pitting in the metal resulting in decreased mechanical stability and an unattractive appearance. Magnesium alloys have insufficient creep resistance for many desirable applications. The hardness of magnesium alloys are very low therefore adhesion and abrasive wear reactions easily happen in these alloy components. Today TIG is the main welding process for magnesium alloys, especially for the removal and repair of casting defects. TIG has some handicaps. Porosity and hot cracks are the most important weld defects. Weld speed is very low in TIG welding. The welds have small weld penetration. Using activating fluxes in TIG welding increased the weld penetration depth. The disadvantages of conventional TIG process have caused attention to be drawn toward Nd: YAG laser welding and laser-TIG hybrid welding processes.
Keywords: Alaşımlar; Metal Eğitimi